KUALITAS PELAYANAN DALAM MENINGKATKAN KEPUASAN NASABAH PADA PT.CENTRAL SANTOSA FINANCE CABANG BANJARMASIN - Diana Hayati; Ni Nyoman Suarniki (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2016)
Abstract, This research aims to analysis customer satisfaction related toservices provided by PT.Central Santosa Finance Branch of Banjarmasin. The method used in this research is descriptive method. The objectof research is PT.CentralSantosa Finance Branch of Banjarmasin. This research found that the service has been done has been good,but based on the results of the research found problems such as slowapplication process, lack of staff at the cashier, a parking area which isstill less extensive and the slow process of completion.